2000
DOI: 10.1086/321183
|View full text |Cite
|
Sign up to set email alerts
|

Splitting Schizophrenia: Periodic Catatonia–Susceptibility Locus on Chromosome 15q15

Abstract: The nature of subtypes in schizophrenia and the meaning of heterogeneity in schizophrenia have been considered a principal controversy in psychiatric research. We addressed these issues in periodic catatonia, a clinical entity derived from Leonhard's classification of schizophrenias, in a genomewide linkage scan. Periodic catatonia is characterized by qualitative psychomotor disturbances during acute psychotic outbursts and by long-term outcome. On the basis of our previous findings of a lifetime morbidity ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
107
1
5

Year Published

2001
2001
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(118 citation statements)
references
References 39 publications
5
107
1
5
Order By: Relevance
“…14 Although CYP1A2 by itself has never been implicated in pathogenesis of schizophrenia, the neighboring loci (15q13-15) have all been implicated. [20][21][22][23] CYP1A2 (15q21) is located in the vicinity of nicotinic receptors CHRNA3, CHRNA5 and CHRNB4, localized at 15q24. CYP1A2 mRNA has been detected in the rat brain (cortex, cerebellum, brain stem, thalamus, hippocampus and striatum 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…14 Although CYP1A2 by itself has never been implicated in pathogenesis of schizophrenia, the neighboring loci (15q13-15) have all been implicated. [20][21][22][23] CYP1A2 (15q21) is located in the vicinity of nicotinic receptors CHRNA3, CHRNA5 and CHRNB4, localized at 15q24. CYP1A2 mRNA has been detected in the rat brain (cortex, cerebellum, brain stem, thalamus, hippocampus and striatum 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chromosome 15q13-15 has been found to be associated with schizophrenia in genome wide scans [30][31][32] although the criteria for linkage were fulfilled in only one study using a subtype Periodic Catatonia (15q15 at position 35.3 cM, LOD score ¼ 3.57, P ¼ 2.6 Â 10 À5 ). 32 Freedman et al 33 reported positive linkage of the abnormality in P50 suppression with D15S1360, a dinucleotide repeat present o120 kbp from the 5 0 end of the coding region of the alpha 7-nicotinic receptor gene (CHRNA-7), assuming an autosomal dominant mode of transmission (LOD score ¼ 5.3, Y ¼ 0.0, Po0.0001 33 ). This linkage has been replicated in several other populations including African Americans, 31 Germans, 32 Southern African Bantu families 34 and Taiwanese.…”
Section: Association Of Cyp1a2 Polymorphisms With Tardive Dyskinesiamentioning
confidence: 99%
“…32 Freedman et al 33 reported positive linkage of the abnormality in P50 suppression with D15S1360, a dinucleotide repeat present o120 kbp from the 5 0 end of the coding region of the alpha 7-nicotinic receptor gene (CHRNA-7), assuming an autosomal dominant mode of transmission (LOD score ¼ 5.3, Y ¼ 0.0, Po0.0001 33 ). This linkage has been replicated in several other populations including African Americans, 31 Germans, 32 Southern African Bantu families 34 and Taiwanese. 35 Several other studies have also pointed towards this region as being of significance for psychiatric disorders.…”
Section: Association Of Cyp1a2 Polymorphisms With Tardive Dyskinesiamentioning
confidence: 99%
“…12 Likewise, Takahashi et al 13 reported suggestive linkage to D22S1169 in subsets of highly familial SZ pedigrees, and a genome scan of catatonic SZ pedigrees found a maximal multipoint LOD score of 2.59 at D22S1169. 14 In BPD linkage has mostly been reported (and examined) at more centromeric regions. In the study of Kelsoe et al, 15 the most significant linkage was found at D22S278 (22q12.3), but positive LOD scores (0.58- 1.22) were also reported at the most telomeric markers tested at 22q13.2-q13.…”
Section: Introductionmentioning
confidence: 99%